Research progress on recent technologies of water harvesting from atmospheric air: A detailed review. (August 2022) - Kandeal, A.W.; Joseph, Abanob; Elsharkawy, Marwan; Elkadeem, M.R.; Hamada, Mohamed A.; Khalil, Ahmed; Eid Moustapha, Moustapha; Sharshir, Swellam W.
Abstract: The increasing of the world population without increasing the natural resources caused water shortage in many regions around the world. Herein is a review of a new freshwater resource depending on harvesting the moisture of the atmospheric air. There are two main methods for extracting water from the ambient air: including composite materials method and cooling the air to the dew point. In the first method, the composite materials absorb the atmospheric air's moisture and regenerate it into drinking water under certain conditions. Researchers have worked on changing the composite material type, and its additives and parameters to improve the productivity of water with acceptable cost. The second method requires just cooling of the atmospheric air until its moisture gets condensed. Power sources based on renewable energy have been developed to drive various techniques, such as vapor-compression cycles, absorption cycles, and Peltier effect-based devices. Beside reviewing different methodologies, this paper focused on the factors that affect the process of extracting water from the air. The formulas for computing the efficiency and water productivity were also mentioned. On the other hand, the research trend of the current topic was analyzed by conducting a comprehensive bibliometric analysis using VOSviewer software based on the Scopus database in the period (1988 – 2021).